Baicalein Exerts Neuroprotective Effects in FeCl3-Induced Posttraumatic Epileptic Seizures via Suppressing Ferroptosis - Li, Qin; Li, Qiu-Qi; Jia, Ji-Ning; Sun, Qian-Yi; Zhou, Hong-Hao; Jin, Wei-Lin; Mao, Xiao-Yuan (Frontiers in Pharmacology, 2019)
Post-traumatic epilepsy (PTE) is a prevalent type of acquired epilepsy secondary to traumatic brain injury, and is characterized by repeated seizures. Traditional antiepileptic drugs have minimal response in preventing post-traumatic epileptic seizures. It is essential for the development of new therapeutic strategy. Our previous work disclosed a potent neuroprotective role of baicalein, a flavonoid extracted from Scutellaria baicalensis Georgi, against inherited epilepsy in rats. Whether baicalein has protective potential in post-traumatic epileptic seizures and the possible molecular mechanism remain elusive. Additionally, the brain is vulnerable to lipid peroxidation-induced damage due to high consumption of oxygen and abundant polyunsaturated fatty acids in neuronal membranes. Our present investigation aimed to elucidate whether baicalein exerts neuroprotective effects on post-traumatic epileptic seizures by inhibiting ferroptosis, a newly discovered lipid peroxidation-dependent cell death modality. We found that baicalein significantly reduced seizure score, number of seizures, and average seizure duration in an iron chloride (FeCl3)-induced PTE mouse model. The neuroprotective effect of baicalein was also validated in a ferric ammonium citrate (FAC)-induced HT22 hippocampal neuron damage model. Moreover, in vitro, baicalein could remarkably decrease ferroptotic indices (lipid reactive oxygen species, 4-hydroxynonenal, and prostaglandin endoperoxide synthase 2) and inhibit the expression of 12/15-lipoxygenase (12/15-LOX) in an iron-induced HT22 cell damage model. These findings were also validated in a mouse PTE model. It was concluded that baicalein exerted neuroprotective effects against post-traumatic epileptic seizures via suppressing ferroptosis and 12/15-LOX was likely to be involved in baicalein’s neuroprotection.